The scarlet letter - Hawthorne, Nathaniel, 1804-1864 (1984)
Set in the harsh Puritan environment of 17th century Boston, The scarlet letter describes the plight of Hester Prynne, an independent-minded woman who stands alone against society. Having given birth to a child after an illicit affair, she refuses to name the father and is forced to wear the letter "A" for adulteress embroidered on her dress
Chapter 1. The Prison-Door -- Chapter 2. The Market-Place -- Chapter 3. The Recognition -- Chapter 4. The Interview -- Chapter 5. Hester at Her Needle -- Chapter 6. Pearl -- Chapter 7. The Governor's Hall -- Chapter 8. The Elf-Child and the Minister -- Chapter 9. The Leech -- Chapter 10. The Leech and His Patient -- Chapter 11. The Interior of a Heart -- Chapter 12. The Minister's Vigil -- Chapter 13. Another View of Hester -- Chapter 14. Hester and the Physician -- Chapter 15. Hester and Pearl -- Chapter 16. A Forest Walk -- Chapter 17. The Pastor and His Parishioner -- Chapter 18. A Flood of Sunshine -- Chapter 19. The Child at the Brook-Side -- Chapter 20. The Minister in a Maze -- Chapter 21. The New England Holiday -- Chapter 22. The Procession -- Chapter 23. The Revelation of the Scarlet Letter -- Chapter 24. Conclusion
First published in 1850
Keywords: Triangles (Interpersonal relations) -- Fiction; Illegitimate children -- Fiction; Women immigrants -- Fiction; Married women -- Fiction; Puritans -- Fiction; Adultery -- Fiction; Revenge -- Fiction; Clergy -- Fiction; Boston (Mass.) -- History -- Colonial period, ca. 1600-1775 -- Fiction; Psychological fiction; Historical fiction